2004
DOI: 10.1074/jbc.m310803200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Mechanistic Implications of N2-(2-Carboxyethyl)arginine Synthase, the First Enzyme in the Clavulanic Acid Biosynthesis Pathway

Abstract: The initial step in the biosynthesis of the clinically important ␤-lactamase inhibitor clavulanic acid involves condensation of two primary metabolites, D-glyceraldehyde 3-phosphate and L-arginine, to give N 2 -(2-carboxyethyl)arginine, a ␤-amino acid. This unusual N-C bond forming reaction is catalyzed by the thiamin diphosphate (ThP 2 )-dependent enzyme N 2 -(2-carboxyethyl)arginine synthase. Here we report the crystal structure of N 2 -(2-carboxyethyl)arginine synthase, complexed with ThP 2 and Mg 2؉ , to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 51 publications
4
28
0
9
Order By: Relevance
“…Controls were run with several proteins that contained an N-terminus consisting of a glycyl, serinyl or threoninyl residue, under the same conditions as those used for hARD1 and HIF substrates. The control proteins were FIH [9], HIF , open reading frames 2 [23], 15 and 16 from the clavulanic acid biosynthesis pathway (unpublished data), and phytanoyl coenzyme A hydroxylase [24], and were donated by D. Lancaster, A. Hardy, Dr. M. Caines and Dr. T. Searls, respectively (Chemistry Research Laboratory, Oxford University).…”
Section: Analysis Of Acetyltransferase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Controls were run with several proteins that contained an N-terminus consisting of a glycyl, serinyl or threoninyl residue, under the same conditions as those used for hARD1 and HIF substrates. The control proteins were FIH [9], HIF , open reading frames 2 [23], 15 and 16 from the clavulanic acid biosynthesis pathway (unpublished data), and phytanoyl coenzyme A hydroxylase [24], and were donated by D. Lancaster, A. Hardy, Dr. M. Caines and Dr. T. Searls, respectively (Chemistry Research Laboratory, Oxford University).…”
Section: Analysis Of Acetyltransferase Activitymentioning
confidence: 99%
“…The resulting GSH-hARD1 was incubated with [1-14 C]-AcCoA and controls were run with several proteins that contained a glycine residue at the N-terminus, under the same conditions as those used for hARD1 and HIF-1a substrates. The control proteins were FIH [9], HIF , open reading frames 2 [23], 15 and 16 from the clavulanic acid biosynthesis pathway, (unpublished data) and phytanoyl coenzyme A hydroxylase [24]. Autoradiographic analysis revealed that the band corresponding to GSH-hARD1 was [ 14 C]-labeled, suggesting that the acetylation was indeed self-mediated; a faint band corresponding to acetylated residual (His) 6 -tagged hARD1 was also visible in assays containing enzyme with both [1-14 C]-AcCoA and ORFs 2, 15 and 16 (Fig.…”
Section: Evaluation Of Hif Fragments and Acth As Substrates For Hard1mentioning
confidence: 99%
“…Three of these steps are catalyzed by a single 2-oxoglutarate (2-OG)-dependent oxygenase, clavaminic acid synthase (CAS2) (10, 18 -20), and one is catalyzed by proclavaminate amidinohydrolase (PAH) (21), to give the bicyclic clavam ring system (22)(23)(24). Crystal structures have been reported for the first four enzymes in the pathway (25)(26)(27)(28) as well as for the gene product of orf6 (OAT2), an ornithine acetyltransferase (29,30) proposed to be involved in the biosynthesis of the L-arginine feedstock for the pathway. The final step in the pathway has also been identified and shown to involve the NADPH-dependent reduction of the labile (3R,5R)-clavaldehyde to give (3R,5R)-clavulanic acid (31).…”
mentioning
confidence: 99%
“…To gain further insights, a fifth type of ceaS2 mutant was created in which the ceaS2 gene was modified by a site-directed mutation of 2 bp, with GA changed to TG, such that the glutamate codon at amino acid 57 became a tryptophan codon. Structural analyses of CeaS2 have suggested that the glutamate residue at position 57 (E57) is intimately involved in the catalytic function of the protein (27), and so the E57W mutant CeaS2 protein was expected to be defective in CeaS2 activity but otherwise unchanged from the wild type. A cloned copy of the E57W mutant version of ceaS2 was conjugated into a ceaS2::apr mutant, whereupon the apr-disrupted ceaS2 was replaced by E57WceaS2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both the ceaS2::apr and ceaS2-FS mutants could potentially produce truncated or C-terminally mistranslated CeaS2 proteins. Since the CeaS protein is known to exist as a tetramer (a dimer of dimers) (27), the defective Ceas2 subunits might interact with active CeaS1 subunits to affect activity.…”
Section: Resultsmentioning
confidence: 99%